2022
DOI: 10.3389/fdgth.2022.974153
|View full text |Cite
|
Sign up to set email alerts
|

“Lock to Live” for firearm and medication safety: Feasibility and acceptability of a suicide prevention tool in a learning healthcare system

Abstract: ObjectiveFew patients with suicide risk are counseled on lethal means safety by health providers. This study tested the feasibility of different delivery methods for Lock to Live (L2L), a web-based decision aid of safe storage options for firearms and medications.MethodsPatients reporting suicide ideation on the PHQ9 depression screener during outpatient health visits were included. Invitation messages to visit L2L were sent via combinations of email, text, Electronic Health Record (EHR) message, mailed letter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Consistent with international design standards [ 23 24 ], the L2L decision aid steps users through various considerations regarding in-home and out-of-home firearm storage options, such as types of storage, costs of storage, and background check requirements, with a goal of encouraging storage solution discussions that are consistent with the users’ values and preferences [ 22 ]. Two subsequent research studies demonstrated promising results for the feasibility and acceptability of offering L2L emergency care encounters [ 25 ] and for the uptake of L2L when it was offered via secure patient portal messages after outpatient care encounters [ 26 ]. Though L2L appears to be a useful tool for supporting suicide prevention in clinical practice, little is known about how to use L2L during routine health care encounters outside of a research context.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with international design standards [ 23 24 ], the L2L decision aid steps users through various considerations regarding in-home and out-of-home firearm storage options, such as types of storage, costs of storage, and background check requirements, with a goal of encouraging storage solution discussions that are consistent with the users’ values and preferences [ 22 ]. Two subsequent research studies demonstrated promising results for the feasibility and acceptability of offering L2L emergency care encounters [ 25 ] and for the uptake of L2L when it was offered via secure patient portal messages after outpatient care encounters [ 26 ]. Though L2L appears to be a useful tool for supporting suicide prevention in clinical practice, little is known about how to use L2L during routine health care encounters outside of a research context.…”
Section: Introductionmentioning
confidence: 99%